2008
DOI: 10.1016/s1658-3876(08)50055-0
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid carcinoma in the United Arab Emirates: perspectives and experience of a tertiary care hospital

Abstract: Thyroid carcinoma in the United Arab Emirates seems to be more common among females and female gender may be a risk factor. Age < 45 years can be considered an important prognostic factor as well as a possible risk factor. PTC predominates the histologic pattern of thyroid carcinoma, which is usually associated with an iodide-sufficient area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
23
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 29 publications
11
23
1
Order By: Relevance
“…Similarly, it is ranked the third most common among Kuwaiti women and second most common among Saudi women 12 . The female predominance observed in this study is similar to those of the previous studies from KSA, UAE, Yemen, Kuwait, Poland, Togo, Turkey, and Brazil 7,9,10,[13][14][15][16][17] . In contrast, thyroid cancer is the 16th most common among females in Ireland 18 .…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, it is ranked the third most common among Kuwaiti women and second most common among Saudi women 12 . The female predominance observed in this study is similar to those of the previous studies from KSA, UAE, Yemen, Kuwait, Poland, Togo, Turkey, and Brazil 7,9,10,[13][14][15][16][17] . In contrast, thyroid cancer is the 16th most common among females in Ireland 18 .…”
Section: Discussionsupporting
confidence: 91%
“…We believe that this difference in the age pattern of BRAF V600E mutation is mainly due to the differences in patients samples between ours and these studies; as most of our PTC samples (70%) are from patients with ages younger than 55 years (Fig 2). In addition, a previous study in the UAE [16] have also shown more than three quarters of PTC cases were diagnosed below the age of 55 years. Geng et al https://doi.org/10.1371/journal.pone.0231341.g002 PLOS ONE [46] have also shown a higher frequency of PTC with BRAF V600E mutation in pediatric age group of less than 10 years of age.…”
Section: Plos Onementioning
confidence: 86%
“…Papillary thyroid carcinoma is the most prevalent type of thyroid cancer worldwide [16]. A lot of works have been done to identify fundamental mechanisms involved in the development of PTC [13,14,[16][17][18][19][20][21]. Many studies have shown a constant rise in the incidence of PTC in different countries all over the world over the last decades [17].…”
Section: Discussionmentioning
confidence: 99%
“…The reported rate of thyroid carcinoma among all malignancies is approximately 1%. In Saudi Arabia, thyroid cancer was the second most common malignancy after breast cancer, while it was reported as the third most common in the United Arab Emirates and fourth most common cancer in Filipino women 9 .…”
Section: Introductionmentioning
confidence: 99%